HUBUNGAN PATIENT SAFETY CULTURE DENGAN PENGALAMAN PERAWAT TERKAIT INSIDEN KESELAMATAN PASIEN DI INSTALASI GAWAT DARURAT (IGD) RSUD dr. ABDUL AZIZ SINGKAWANG TAHUN 2023 - azzahra, fatima; Limson, Leonatus; Suhariyanto, Suhariyanto (Poltekkes Kemenkes Pontianak, 2023)
ABSTRACT The Emergency Department is the entrance to the hospital where all patient services start here. Adverse Events (AE) are of particular concern at this time. From January to September, RSUD dr. Abdul Aziz in 2022 already has 12 reports. One of the shapers of patient safety was the Patient Safety Culture (PSC) where this PSC consists of twelve mutually sustainable dimensions. Through this research, it can be the basis for the development of patient safety in a better direction by knowing the relationship between patient safety culture (PSC) and Adverse Events (AE) in the emergency room (ER). This research design was in the form of observational analytic cross-sectional with quantitative methods. The study used the Hospital Survey On Patient Safety Culture (HSOPSC) questionnaire instrument from the Agency for Healthcare Research and Quality (AHRQ). The total sample was 18 nurses with the Total Sampling technique. Data analysis using Pearson Product Moment (PPM) was processed through SPSS 25. From this study, the results were obtained that the Patient Safety Culture in the Emergency Department nurses of dr Abdul Aziz Hospital was positive at 83.94%, and the nurses’ experience about adverse events (AE) was low at 29.3%. The relationship between PSC and Nurses’ Experience About Adverse Events (AE) was significant, with a p-value of 0.029 >0.05 and an rvalue = -0.514 with a negative correlation direction and variable contribution of 26.41%. There was a significant influence related to patient safety culture (PSC) with nurses’ experience about adverse events (AE) at the emergency department (ER) of RSUD dr. Abdul Aziz Singkawang in 2023Keywords : Patient Safety Culture, Nurses’ Experience, Adverse Events, Emergency Department ABSTRAK Instalasi Gawat Darurat merupakan pintu masuk rumah sakit dimana semua pelayanan pasien bermula disini. Insiden keselamatan pasien menjadi perhatian khusus saat ini. RSUD Abdul Aziz sendiri pada tahun 2022 dari bulan Januari sampai September sudah memiliki 12 laporan. Salah satu pembentuk dari keselamatan pasien adalah Patient Safety Culture (PSC) dimana PSC ini terdiri dari duabelas dimensi yang saling berkesinambungan. Melalui penelitian ini dapat menjadi dasar untuk pengembangan keselamatan pasien kearah yang lebih baik dengan mengetahui hubungan hubungan patient safety culture (PSC) dengan insiden keselamatan pasien di instalasi gawat darurat (IGD). Desain penelitian ini berupa observasional analytic crosssectional dengan metode kuantitatif. Penelitian menggunakan instrumen kuesionse Hospital Survey On Patient Safety Culture (HSOPSC) dari Agency for Healthcare Research and Quality (AHRQ) untuk pengukuran Patient Safety Culture dan kuesioner dari Hilda et.al, 2018. Total sampel sebanyak 18 orang perawat dengan teknik pengambilan sampel Total Sampling. Analisa data menggunakan Pearson Product Moment (PPM) yang diolah melalui SPSS 25. Dari penelitian ini didapatkan hasil yaitu Patient Safety Culture pada perawat Instalasi Gawat Darurat RSUD dr. Abdul Aziz bernilai positif yaitu 83.94% dan Insiden Keselamatan Pasien rendah 29.3%. Hubungan antara PSC dan IKP signifikan dengan nilai p-value 0.029>0.05 dan nilai r = -0.514 dengan arah korelasi negatif serta kontribusi variabel sebesar 26.41%. Terdapat pengaruh yang signifikan terkait Patient Safety Culture (PSC) dengan insiden keselamatan pasien di Instalasi Gawat Darurat (IGD) RSUD dr. Abdul Aziz Singkawang tahun 2023